Bunuzdogbe musical tradition among the Aganyin of Lagos, Nigeria (2016)
The Aganyin of Lagos are immigrants from then Gold Coast now Ghana into Nigeria and they have largely settled around the Coastal areas of Badagry Local Government in Lagos State since around the 16th Century. Given the dearth of studies on the socio-cultural practices of the Aganyin, particularly their music, this paper examines the musical tradition among the Aganyin of Lagos. Participant observation and In- depth Interview were used to collect data for the study. This study reveals that bunudzogbe music, a social music, is characterized by three musical movements during performance. Afahun with moderately fast tempo is the opening movement, and it takes the form of songs of praise and prayer. Gbaja is the second movement. It is very fast and involves full participation. Its lyrics are satirical, and they contain warnings and social Sentiments. The last movement, Ageshe, has a moderate tempo. This paper concludes that bunudzogbe musical tradition fosters social bonding among the Aganyin and enhances inter- culturality with their host Community